PERBANDINGAN FAKTOR-FAKTOR YANG MEMPENGARUHI UTANG LUAR NEGERI NEGARA-NEGARA ANGGOTA ASEAN (Studi pada Indonesia dan Philippines periode 1970-2014) - Sari, Tri Puji Ratna (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to determine the factors that influence the external debt in Indonesia and the Philippines the period 1970 to 2014 in the short term and long term. Variables used in this research is the exchange rate, inflation, GDP, exports, and savingThe method used in this study is a model of Error Correction Model (ECM) Engle Granger. Results from this study is their long-term relationship between a variable rate, inflation, GDP, and saving against Indonesia external debt. And the existence of a long-term relationship between a variable rate, GDP, and saving on foreign debts in Philippines.Selain it in the short term in the Philippines, there are several factors that influence such as inflation, GDP, and saving.Keywords: Exchange Rate, Inflation, GDP, Saving, External Debt